Pengaruh Gaya Kepemimpinan Transformasional, Budaya Organisasi dan Inovasi terhadap Kinerja (Studi pada Panti Asuhan di Kota Tomohon dan Kabupaten Minahasa) - Bhikkhu Dharma Suryo (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2010)
The condition of the present-day modern society with its huge advances in science and technology indicates that such advances in very influential for the management of organizations, especially in terms of leadership transformational and performance of the managers in an organization. It means that managing an orphanage should be based on professional leadership. The leadership transformational style of an organization should be able to lead to a process of building a collective and individual effort in mutual cooperation to implement the activities and achieve the common objectives. The question of this research is related to the paradigm of the effect of leadership transformational style, organizational culture and innovation towards performance. This research aims to contribute ideas for the leaders in orphanages in terms of leadership transformational style, organizational culture and organizational performance. Considering the problems of the research, this research can be classified as explanatory research that is a research that aims to describe the relation between variables. This research requires primary and secondary data and the respondent for this research is all leaders of orphanages in the municipality of Tomohon and Regency of Minahasa, altogether 216 respondents. The sample was taken using purposive method. In order to test the impact of each variable, structural equation modeling (SEM) is used. The result of the research shows that there are six points of findings. The result of research shows that leadership transformational styles influence organizational culture, leadership transformational styles influence innovation, organizational culture influence innovation, leadership transformational style is not influence management performance, organizational culture influence management performance, innovation influence management performance. The six findings indicate that the proposed hypotheses are acceptable. This research offer a model of leadership based on review of literature and the proposed model basically emphasizes the importance of a leadership transformational style that is oriented towards innovation, an organizational culture can adapt to innovation, and innovation that always brings renewal of organization to facilitate the achievement of management’s performance.Keywords: Leadership transformational, organizational culture, innovation, performance, adaptation